From Saturday night to Sunday night : my forty years of laughter, tears, and touchdowns in TV - Ebersol, Dick (Simon & Schuster, 2022)
"A memoir by the legendary television executive detailing his pioneering work on Saturday Night Live, Sunday Night Football, the Olympics, the NBA, music videos, late night, and more."--Amazon.